Propuesta de elaboración de política pública en materia de seguridad ciudadana para el Gobierno Autónomo Descentralizado del cantón Bolívar - Cedeño Navarrete, Mariela Alexandra (2022)
The decentralized autonomous municipal governments of Ecuador do not have the absolute powers to cover all security problems within their territory and thus provide citizens with the necessary guarantees to be able to carry out their activities safely. However, within the legal and juridical regulations that govern and regulate the functioning of the powers of the state at its different levels, they establish certain attributions to the Municipal GADS. Hence, the objective of this research was to propose strategies and actions for the development of public policy on citizen security in the Bolívar canton. To diagnose the criminal situation, records from the National Police on crime levels (2014-2020) were obtained. Regression techniques, such as analysis of variance, were performed to rank the averages obtained. Structured interviews and survey techniques were applied with an accuracy of 95%. Principal component analysis and discriminant analysis were applied to characterize the interviewees. Obtaining the following results: An inversely proportional relationship between crime and time was obtained. The fusion was the following Relative Crime Frequency = -0.0168*years+34.09. The factor that decreased crime was the COVID-19 pandemic. According to the interview and survey, there is no Citizen Security Plan (PSC) within the canton. Rejecting the null hypothesis raised in this investigation. There were three types of citizens with different credibility in relation to participatory and community security within the canton. A PSC proposal is proposed based on: Diagnosing the citizen security situation, generating a citizen security proposal with multidisciplinary and inter-institutional participation and programmatically structuring the interventions by strategy and objectives to ground the public security policy within the canton.